Prognosis for ballistic sensitivity of pre-notch in metallic beam through mesh-less computation reflecting material damage. (15th August 2015) - Chakraborty, Sukanta; Shaw, Amit
Abstract: Pre-existing discontinuity in the form of notch in a clamped metallic beam can significantly alter its final response and failure pattern under a dynamic impact event. The extent of the notch's influence and sensitivity of its underlying parameters are numerically investigated in this work. Based on Smoothed Particle Hydrodynamics (SPH), a computational framework is developed which can account for material damage and possible moving physical discontinuity due to propagation of crack from the notch location. The numerical model is first validated with experimental evidences from literature and then further explored to establish a mechanism to estimate the precise effects of each of the controlling parameters that may affect dynamic response of clamped beam under impact. Movement of plastic flow and its interaction with geometric irregularity causing localised plastic deformation is studied. Finally a potential deterministic approach is followed to predict the critical velocity for a beam with particular impedance and with certain pre-notch geometry.